In pursuit of Sustainable Development Goal (SDG) number 7: Will biofuels be reliable?. (August 2017) - Acheampong, Michael; Ertem, Funda Cansu; Kappler, Benjamin; Neubauer, Peter
Abstract: Driven by the desire to mitigate climate change and reduce overdependence on fossil fuels, biofuels have been actively pursued in recent years because they are believed to be inherently environmentally friendly. In the past few years, however, critics have objected to the basis for which it should be adopted due to potential negative trade-offs. Sustainable Development Goals (SDG) number seven seeks to substantially increase contribution of renewable energy to global energy supply, as well as double the rate of improvement in efficiency of energy. Biofuels are likely to play a key role in the pursuit of these goals being one of the most advanced alternative energy sources. This review assesses the potential of biofuels to contribute to the set SDGs by presenting an appraisal of their development over the years. It sheds light on some main arguments surrounding biofuels from the perspective of proponents and critics alike. Even though biofuels have a great potential in aiding climate change mitigation, its large scale adoption is regarded as problematic in its current state. This is because of its potential negative trade-offs in terms of land use change and emissions, especially for first and second generation biofuels. However, a combination of plant biology, carbon capture techniques and novel bioconversion processes provided by third and fourth generation biofuel technologies have set open an era of fuels that will be abundant, energy efficient and clean to support the seventh SDG.